Fiscal Consolidation to Accelerate Growth and Support Inclusive Development : Ghana Public Expenditure Review - World Bank (Washington, DC, 2017)
Ghana has experienced an extended period of robust growth since the early 2000s, supported by a favorable external environment and large investment inflows, particularly in the extractive industries. In 2011, as the start of oil production drove a surge in per capita income, Ghana graduated from low-income to lower-middle-income status. Despite the key role of the extractive industries, recent growth has been relatively inclusive, and Ghana achieved its Millennium Development Goal of halving the poverty rate by 2015. However, macroeconomic conditions have deteriorated since 2012, giving rise to substantial domestic and external imbalances. Although external shocks have underscored Ghana's vulnerability to global commodity and financial markets, the recurring nature of its imbalances reflects deeper structural deficiencies in its macroeconomic policies and public financial management (PFM) framework. A heavy focus on commodity exports has accelerated Ghana's recent growth, but the country's economic outlook increasingly hinges on a narrow range of volatile commodity prices.